Clown : the physical comedian - Dieffenbacher, Joe (London, England : Zed Books, 2021)
"Clown: The Physical Comedian is a detailed and comprehensive workbook for those interested in the art of clowning and physical theatre, including actors, directors, improvisers, stand-up comedians, circus artists, mask performers and devisers of new work. Offering an extensive and hugely diverse compilation of tried-and-tested exercises and games, the book is for students, teachers and practitioners to aid ensemble-building, character development, devising theatre, physicalising text and vocalising movement, plus creating cabaret acts, clown routines and adding physical play to scripted scenes. It offers advice on subjects such as developing presence onstage; increasing strength, flexibility and physical expression; developing partner and trio relationships; understanding the power of the mask; and working with an audience - in particular, turning a performance into a conversation with the audience and increasing the actor's ability to connect with a crowd. The exercises and teachings have been developed in classrooms, workshops and theatres all over the world and the book is packed with insights from the author, who has worked for over 35 years in a wide variety of venues, from intimate performance spaces to large-scale sports stadiums"--
The fundamentals -- Challenges and obstacles -- Hello : a pharmacist, helium balloons, and a red nose -- Energy : the telepathic renaissance fool -- The talking body : silence on the streets -- Prop play : the prop whisperer -- Curiosity : oddfellows -- Clown solos : catching a salad on your face -- Clown duos : the wet towel intervention -- Clown trios : boss, negotiator, fool -- Clown ensembles : fractious fun -- The rules, the script, the game, the play : welcome to the playroom -- The mask of the clown -- The skillful clown -- Getting serious about your funny -- Devising for clown and physical comedy.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Clowning -- Handbooks, manuals, etc; Acting techniques; Electronic books